2011
DOI: 10.1007/s11060-011-0549-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induces matrix metalloproteinase-1 (MMP-1) expression and invasion in glioma cell lines via the MAPK pathway

Abstract: Glioblastoma multiforme (GBM) is an aggressive cancer with a poor survival rate. A key component that contributes to the poor prognosis is the capacity of glioma cells to invade local brain tissue in a diffuse manner. Among various proteases that aid in the process of invasion, matrix metalloproteinase-1 (MMP-1) has been identified as an important contributory factor in various cancers. Apart from its traditional role in cleaving its primary extracellular matrix (ECM) substrates, and like other members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 20 publications
(25 reference statements)
1
46
0
1
Order By: Relevance
“…Additionally, expression of collagenases, such as MMP-1 and MMP-13, is deregulated in various cancers (9). MMP-1 expression has been documented to occur in GBM cells (4,21), and increased expression correlates with increased tumor grade (58,71) and tumorigenicity (52), and decreased survival in GBM patients (71). Moreover, increased MMP-13 production in glioma cells in response to various stimuli leads to an increase in migration and invasion (43).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, expression of collagenases, such as MMP-1 and MMP-13, is deregulated in various cancers (9). MMP-1 expression has been documented to occur in GBM cells (4,21), and increased expression correlates with increased tumor grade (58,71) and tumorigenicity (52), and decreased survival in GBM patients (71). Moreover, increased MMP-13 production in glioma cells in response to various stimuli leads to an increase in migration and invasion (43).…”
Section: Discussionmentioning
confidence: 99%
“…MAP Kinases were considered as the most important kinases involved in mechanotransduction (Wang and Thampatty, 2006). Many evidences showed that MMPs expression induced by chemical and physical factors were related to MAP Kinases pathway (Anand et al, 2011;Brauchle et al, 2000;Kook et al, 2011). Indeed, fluid shear stress rapidly activated ERK, P38 and JNK in 5-10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled by activation of RAS at the cell surface interior, the subsequent stimulation of Raf and then MEK and ERK serves to regulate a range of key intracellular effectors associated with cell proliferation, 1 invasion, 2 angiogenesis, 3 and apoptotic resistance. 4 Mutated RAS is associated with almost one-third of human cancers, and a majority of malignant melanomas and papillary thyroid cancers harbor B-Raf mutations.…”
mentioning
confidence: 99%